2019
DOI: 10.1111/cns.13111
|View full text |Cite
|
Sign up to set email alerts
|

Nasal delivery of Fasudil‐modified immune cells exhibits therapeutic potential in experimental autoimmune encephalomyelitis

Abstract: Summary Aim Multiple sclerosis (MS) is a relapsing‐remitting inflammatory demyelinating disease that requires long‐term treatment. Although Rho kinase inhibitor Fasudil shows good therapeutic effect in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, certain side effects may limit its clinical use. This study aimed at observing the therapeutic potential of Fasudil‐modified encephalitogenic mononuclear cells (MNCs) via nasal delivery in EAE and exploring possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It was indicated that endogenous and exogenous IL-10 could directly or indirectly inhibit the production of pro-inflammatory factors, such as IL-1β, and the proliferation of T cells, thus blocking elicitation of the immune response and reducing inflammatory damage in a severe colitis mouse model [ 3 ]. Subsequently, CD4 + IL-10 + T cells were shown to exert immunosuppressive effects in various disease models, such as inflammatory bowel disease (IBD) and experimental autoimmune encephalomyelitis (EAE) [ 4 , 5 ]. Our previous results showed that hPMSCs could alleviate GVHD symptoms by maintaining the balance of CD4 + IL-10 + T cells and Th17 subsets [ 6 ]; however, the specific mechanism by which hPMSCs regulate the generation of CD4 + IL-10 + T cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that endogenous and exogenous IL-10 could directly or indirectly inhibit the production of pro-inflammatory factors, such as IL-1β, and the proliferation of T cells, thus blocking elicitation of the immune response and reducing inflammatory damage in a severe colitis mouse model [ 3 ]. Subsequently, CD4 + IL-10 + T cells were shown to exert immunosuppressive effects in various disease models, such as inflammatory bowel disease (IBD) and experimental autoimmune encephalomyelitis (EAE) [ 4 , 5 ]. Our previous results showed that hPMSCs could alleviate GVHD symptoms by maintaining the balance of CD4 + IL-10 + T cells and Th17 subsets [ 6 ]; however, the specific mechanism by which hPMSCs regulate the generation of CD4 + IL-10 + T cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…126 Intranasal administration of the entire cells was also attempted with a reported moderate positive effect. [134][135][136] Indeed, cells can migrate in to the CNS after being administered by intranasal delivery. 135 Moreover, a couple of studies reported efficacy of the intranasal microvesicles therapy in a preclinical scenario.…”
Section: Intranasalmentioning
confidence: 99%
“…Production and release of EVs is one of the major modes of action of cells used in cell therapy 126 . Intranasal administration of the entire cells was also attempted with a reported moderate positive effect 134–136 . Indeed, cells can migrate in to the CNS after being administered by intranasal delivery 135 .…”
Section: Alternative Drug Delivery Strategiesmentioning
confidence: 99%
“…The Fasudil, a potent ROCK inhibitor has been approved for clinical use in Japan for the treatment of subarachnoid hemorrhage, and cerebral vasospasm. It was also shown to increase motor neuron survival, and inhibit axonal degeneration, enhances axonal regeneration, and modulates microglial function in vitro and in vivo (Bandarage et al, 2021;De et al, 2019;Koch et al, 2020;Mietzner et al, 2020;Román-Albasini et al, 2020;Tatenhorst et al, 2016;Wang et al, 2020;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%